A phase I/II pilot study assessing the preliminary efficacy of wall climbing for improving posttraumatic growth and quality of life in gynecologic cancer survivors. (October 2016) - Crawford, Jennifer J.; Vallance, Jeff K.; Holt, Nicholas L.; Steed, Helen; Courneya, Kerry S.
Abstract: Objective: We previously reported a pilot randomized controlled trial in gynecologic cancer survivors (GCS) suggesting that wall climbing is safe, feasible, and improves objective physical functioning. Here, we report the effects of wall climbing on posttraumatic growth, quality of life, and symptoms. Methods: GCS (N = 35) were randomized to either an 8-week wall climbing intervention (WCI; n = 24) or usual care (UC; n = 11). The primary efficacy outcome was posttraumatic growth assessed by the Posttraumatic Growth Inventory. Secondary outcomes included health-related quality of life assessed by the Short Form-36 (SF-36). Results: Analyses of covariance revealed a statistically significant or borderline significant effect favoring WCI over UC for the posttraumatic growth subscales of new possibilities (d = + 0.70; p = 0.065) and personal strength (d = + 0.76; p = 0.049) as well as the SF-36 mental health subscale (d = +0.61; p = 0.077) and the mental health component score (d = +0.80; p = 0.063). Conversely, a statistically significant or borderline significant effect favoring UC over WCI was found for the SF-36 bodily pain subscale (d = −0.50; p = 0.063) and the physical health component score (d = −0.58; p = 0.038). Conclusions: This phase I/II study suggests that wall climbing may improve some aspects of posttraumatic growth and mental health in GCS but may also cause some bodily pain and reduced physical health. Larger phase II and III trials are needed to fully describe the potentially complex benefits and harms of wall climbing in GCS. Highlights: Wall climbing may prompt posttraumatic growth in gynecologic cancer survivors. Wall climbing may prompt improved mental health in gynecologic cancer survivors. Survivors who wall climbed reported increased bodily pain and reduced physical health.